Evidence from simulation studies for selective constraints on the codon usage of the Angiosperm psbA gene - Antonina Kalkus (Public Library of Science (PLoS), 2021)
The codon usage of the Angiosperm psbA gene is atypical for flowering plant chloroplast genes but similar to the codon usage observed in highly expressed plastid genes from some other Plantae, particularly Chlorobionta, lineages. The pattern of codon bias in these genes is suggestive of selection for a set of translationally optimal codons but the degree of bias towards these optimal codons is much weaker in the flowering plant psbA gene than in high expression plastid genes from lineages such as certain green algal groups. Two scenarios have been proposed to explain these observations. One is that the flowering plant psbA gene is currently under weak selective constraints for translation efficiency, the other is that there are no current selective constraints and we are observing the remnants of an ancestral codon adaptation that is decaying under mutational pressure. We test these two models using simulations studies that incorporate the context-dependent mutational properties of plant chloroplast DNA. We first reconstruct ancestral sequences and then simulate their evolution in the absence of selection on codon usage by using mutation dynamics estimated from intergenic regions. The results show that psbA has a significantly higher level of codon adaptation than expected while other chloroplast genes are within the range predicted by the simulations. These results suggest that there have been selective constraints on the codon usage of the flowering plant psbA gene during Angiosperm evolution. Author summary We simulated the evolution of four photosynthesis genes that are coded by the chloroplast genome of flowering plants in order to investigate the role of natural selection. In particular we were interested in whether or not selection can influence the evolution of features that do not affect the protein coded by the gene but that do affect the expression of the gene. We developed a model of mutation and then assume that there is no selection in simulations to generate expected patterns of evolution. Importantly, our mutation model accounts for a complex feature of chloroplast DNA which is that nucleotides near the site mutating affect the type of mutation that occurs. We found that one gene in particular has not evolved as predicted by our simulations but, rather, has evolved in a manner that suggests that mutations which affect the level of gene expression have been under natural selection.